Analisa Pengaruh Casting Speed dan Superheat Terhadap Cacat Permukaan Slab Baja Grade 1A0804 - Herdi Susanto (universitas teuku umar, 2018)
Increasing the life of the continuous casting machine causes a defect on the surface of the steel slab, it takes some corrective measures for the casting process, such as by redefining and updating the standard operating parameters that influence the casting process with a review of the surface defects. This research was conducted at the Division of Steel Slab Plant II PT. Krakatau Steel using casting machine kontiyu Low head machine with a straight mold, angle and transverse crack at grade steel slab 1A0804. The result showed the operating parameters are better at ≤ 1.30 casting speed <1.35 m/min and 250 <superheat ≤ 300 C. From these results it can be concluded that the standard operating parameters of continuous casting to casting speed of 1.4 m / min is important to be updated and superheat 300C can still be used Keywords : steel 1A0804, casting speed, superheat, angle crack, transverse crack